2012
DOI: 10.1007/s10877-012-9362-0
|View full text |Cite
|
Sign up to set email alerts
|

A model-based decision support system for critiquing mechanical ventilation treatments

Abstract: A computerized system for critiquing mechanical ventilation treatments is presented that can be used as an aide to the intensivist. The presented system is based on the physiological model of the subject's respiratory system. It uses modified versions of previously developed models of adult and neonatal respiratory systems to simulate the effects of different ventilator treatments on the patient's blood gases. The physiological models that have been used for research and teaching purposes by many researchers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…RS1 is the respiratory model described in Fincham and Tehrani ( 1983 ) which has been extensively studied by many researchers for teaching and research purposes (Mañanas et al, 2003 ; Tehrani et al, 2004 ; Batzel et al, 2007 ; Hernandez et al, 2008 ). Additionally, it has been used to predict the effects of ventilatory settings on blood gases of mechanically ventilated patients and to adjust the ventilation parameters to optimize such a treatment both adult and infant (Tehrani and Abbasi, 2012 ). A schematic diagram of this model is provided in the Supplementary Material Section (see Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…RS1 is the respiratory model described in Fincham and Tehrani ( 1983 ) which has been extensively studied by many researchers for teaching and research purposes (Mañanas et al, 2003 ; Tehrani et al, 2004 ; Batzel et al, 2007 ; Hernandez et al, 2008 ). Additionally, it has been used to predict the effects of ventilatory settings on blood gases of mechanically ventilated patients and to adjust the ventilation parameters to optimize such a treatment both adult and infant (Tehrani and Abbasi, 2012 ). A schematic diagram of this model is provided in the Supplementary Material Section (see Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In models (13) and (14), x is the vector of decision variables representing the model inputs, namely the patientspecific parameters and the controls. The l and u represent lower and upper bounds on the inputs as defined in Table 3.…”
Section: Robustness Of the Modelmentioning
confidence: 99%
“…After fixing these variable values, the resulting vector x had dimension 11 under pressure support and dimension ten under proportional assist. Viewed as multi-objective optimization problems with three objective functions, our goal was to generate an approximate Pareto optimal set for models (13) and (14). The Pareto optimal set is defined as the set of "non-dominated" output values {ΔP L (x), |ΔP ES (x)|, pH(x)}, i.e., those that cannot be improved upon simultaneously in all three indicators and where improvement in any one of the indicators necessarily results in a degradation in the others.…”
Section: Robustness Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Several groups have begun work in this area, although no such platform was identified that is, as yet, widely available. [42][43][44][45][46][47] One likely difference between pediatric and adult ventilator management practices lies in the former's reliance on noninvasive but continuous "blood gas" measurements over the adult intermittent measurement of arterial blood gas data. For example, pediatric intensivists more often monitor SpO 2 over PaO 2 .…”
Section: Beyond If…then Rulesmentioning
confidence: 99%